Who could ever love you [compact disc, unabridged] - Trump, Mary L. (Macmillan Audio, 2024)
Mary Trump grew up in a family divided by its patriarch's relentless drive for money and power. The daughter of Freddy Trump, the highly accomplished, dashing eldest son of wealthy real estate developer Fred Trump, and Linda Clapp, a flight attendant from a working-class family, Mary lived in the shadow of Freddy's humiliation at the hands of his father. Fred Trump embodied the ethos of the zero-sum game and among his five children, there could only be one winner. That was supposed to be Freddy, his namesake, but Fred found him wanting, too sensitive, too kind, too interested in pursuits beyond the realm of the real estate empire he was meant to inherit. In Donald, Fred found a kindred spirit, a "killer," who would stop at nothing to get his own way. Even after Freddy's short-lived career as a professional pilot for TWA came to an end, he never stopped trying to gain his father's approval. Finally, at the age of forty-two, he succumbed to Fred's lethal contempt and died alone in an emergency room, with no family by his side. Mary Trump brings us inside the twisted family whose patriarch ignored, froze out, and eventually destroyed his own. Freddy Trump's decline into alcoholism and illness, along with Linda's suffering after their divorce, left Mary dangerously vulnerable as a very young girl. Inadequately and only conditionally loved, there were no adults in her life except for the father she loved, but lost before she could know him; and a mother abandoned by her ex-husband's rich and powerful family who demanded her loyalty but left her with nothing. With searching insight, poignant detail, and unsparing prose, Mary Trump reveals the cold, selfish cruelty that has come to define the Trump family thanks in large part to her uncle, whose malignant ambition has riven our nation and threatens the world.